The Effect of HDI, Population Density, Poverty, and Income Inequality on Criminality in DKI Jakarta Province - May Putriana Margaretha Br. Sitanggang; Hutapia Hutapia (Universitas Bangka Belitung, 2024)
The purpose of this study is to examine how the human development index, population density, poverty rate, and income inequality affect the crime rate in DKI Jakarta Province from 2014 to 2022. The data used in this study came from the Central Bureau of Statistics (BPS). The method used is panel data regression with the Common Effect Model (CEM) which is the best model. The results showed that the level of human development, population, and poverty had a positive and significant impact on the crime rate in DKI Jakarta Province from 2014 to 2022. Meanwhile, income inequality has a positive but insignificant effect on the crime rate. Together, the human development index (HDI), population density, poverty rate, and income inequality affect the crime rate in DKI Jakarta Province from 2014 to 2022.